NEAR-FIELD DIPOLE RADIATION DYNAMICS THROUGH FDTD MODELING - Radzevicius S.J.; Chen C.C.; Peters L.; Daniels J.J. (My University, 2003)
We use finite-difference time-domain (FDTD) numerical simulations to study horizontal dipole radiation mechanisms and patterns near half-space interfaces. Time snapshots illustrating propagation of wavefronts at an instance in time are included with antenna patterns to provide a visualization tool for understanding antenna radiation properties. Near-field radiation patterns are compared with far-field asymptotic solutions and the effects of electrical properties, antenna height, and observation distance are investigated through numerical simulations. Numerical simulations show excellent agreement with measured data collected over a water-filled tank. Near-field H-plane radiation patterns are broader and contain radiation maxima beyond the critical angle predicted by far-field solutions. A large amplitude E-plane radiation lobe is located directly below the antenna in all simulations, while the two large amplitude sidelobes are less distinct and occur at larger incidence angles than predicted by far-field solutions. Radiation patterns resemble far-field solutions by a distance of 10 wavelengths, except near the critical angle where H-plane radiation maxima and E-plane sidelobes occur at larger incidence angles than predicted by far-field solutions.
Keywords: GPR; RADIATION PATTERNS; DIPOLE ANTENNAS; FDTD MODELING